Clinical evaluation of microendoscopy-assisted extreme lateral interbody fusion - Segawa, Tomohide; Inanami, Hirohiko; Koga, Hisashi (Journal of Spine Surgery; Vol 3, No 3 (September 29, 2017): Journal of Spine Surgery, 2017)
Background: Extreme lateral interbody fusion (XLIF) has rapidly become a popular operative procedure for lumbar canal stenosis and scoliosis. This approach provides direct access to the lateral aspect of the disc with minimal disruption of spinal structures, including ligaments and muscles. However, it involves risk of injuries to the lumbar nerve plexus, segmental artery and intestinal tract because of the limited surgical field. This study aimed to clarify the benefit of using a microendoscope to prevent these injuries. Methods: A total of 96 consecutive patients treated by a single surgeon were retrospectively analyzed. The basic approach via the psoas muscle was performed in accordance with the conventional XLIF procedure. Operative manipulations, such as insertion of the shim, discectomy, endplate preparation and intervertebral spacer placement, were performed with the assistance of a microendoscope. Preoperative and postoperative neurological status were evaluated using the Japanese Orthopedic Association (JOA) scores and the Oswestry Disability Index (ODI). Results: Eighty-four patients underwent surgery for a single vertebral level, nine patients underwent surgery for 2 levels and three patients underwent surgery for 3 levels (average, 1.2 levels). The average age of patients was 61 years (range, 22–83 years); the mean follow-up period was 18 months (range, 3–36 months). Average preoperative and postoperative JOA scores were 11.9 and 15.6, with a mean recovery rate of 33%. Average preoperative and postoperative ODI scores were 38.6 and 19.1. There were 3 (3.1%) complications: 2 end-plate fractures and 1 deep surgical site infection. There were no bowel perforations or vascular injuries. Conclusions: Microendoscopy assistance is one solution for severe visceral and vascular injuries related to XLIF.